The influence of raw material inventory management and machine maintenance on the production process - Badrudin, Ahmad; Mukhsin, Moh; Satyanegara, Diqbal (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
This study aims to determine the effect of raw material inventory management and machine maintenance on the All Aluminum Alloy Conductor-Shielded (AAAC-S) cable production process at PT. Pulung Cable Indonesia. The method used in this research is quantitative with a causal associative approach. The population used in this study were all employees of PT. Pulung Cable Indonesia. The sample in this study is part of the population of all employees of PT. Pulung cable Indonesia using non-probability technique by purposive sampling. The data analysis technique used is multiple linear regression analysis using the SPSS 22 software program for windows. The results of this study indicate that: (1) Raw material inventory management has a positive and significant effect on the production process. (2) Machine maintenance has a positive and significant effect on the production process.